Evaluation of Reports from the Environmental Management Plan and Environmental Monitoring Plan at the Palm Oil Mill in Bengkalis Regency, 2022 - Marngatin Marngatin; Oktavia Dewi; Kamali Zaman; Herniwanti Herniwanti; Endang P. Rahayu (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze evaluation of reports from the environmental management plan and environmental monitoring plan at the Palm Oil Mill in Bengkalis Regency in 2022. The research is conducted using qualitative research and case study research design. Information related to the operational impact of Palm Oil Mill on environmental health is obtained through key informant who is given the IK code, the main informant is given the IU code, and the supporting informant is given the IP code. The equipment used in this study includes observation sheets and survey sheets (checklist table) as well as interview guides (questionnaires) which were compiled and designed by the authors based on applicable regulations, and general theories sourced from related literature. The data analysis technique used in this qualitative research has several stages, namely data reduction, data presentation, coding categories, and drawing conclusions. The results show that Bengkalis Regency Environmental Service has not carried out an evaluation of the environmental management plan and environmental monitoring plan reports that have been submitted by the company.